1973
DOI: 10.1111/j.1365-3091.1973.tb01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and nature of incorporation of trace elements in modern aragonitic corals*

Abstract: The objective of this study is to locate as closely as possible the sites of strontium, magnesium, sodium, and potassium in modern aragonitic corals, specifically whether these cations are adsorbed, or are substituted in the carbonate lattice or are incorporated in organic components. In addition to locating the sites of each of these four elements we wanted to find out quantitatively how much of each element occurs at each site. The experiments in this study are based on the dissolution rate of aragonite in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 20 publications
3
61
0
4
Order By: Relevance
“…It is known that significant amounts of Na and Mg are adsorbed, as ionic forms, on the surface of coral skeletons and that the ions adsorbed on the skeletal surface can be removed by treating the skeletons with distilled/ deionized water (DDW) or a very weak acid solution (e.g., Amiel et al, 1973;Yoshioka et al, 1985Yoshioka et al, , 1986Mitsuguchi et al, 2001;Watanabe et al, 2001b). Our element/Ca ratio data are probably completely free from the influence of such adsorption, because we treated coral samples with DDW, very dilute HNO 3 and H 2 O 2 , under ultrasonic agitation (see Section "Materials and Methods").…”
Section: Indicate Results Of 5 Coral Powder Samples (Shown As Differementioning
confidence: 99%
See 1 more Smart Citation
“…It is known that significant amounts of Na and Mg are adsorbed, as ionic forms, on the surface of coral skeletons and that the ions adsorbed on the skeletal surface can be removed by treating the skeletons with distilled/ deionized water (DDW) or a very weak acid solution (e.g., Amiel et al, 1973;Yoshioka et al, 1985Yoshioka et al, , 1986Mitsuguchi et al, 2001;Watanabe et al, 2001b). Our element/Ca ratio data are probably completely free from the influence of such adsorption, because we treated coral samples with DDW, very dilute HNO 3 and H 2 O 2 , under ultrasonic agitation (see Section "Materials and Methods").…”
Section: Indicate Results Of 5 Coral Powder Samples (Shown As Differementioning
confidence: 99%
“…The slab was ultrasonically cleaned in distilled/ deionized water (DDW) and dried, then X-rayed. The Xradiography revealed coral skeletal growth patterns and Element/Ca ratio General range (mmol/mol) References Na/Ca 15−24 Amiel et al (1973), Land and Hoops (1973), Polyakov and Krasnov (1976), Swart (1981), Oomori et al (1982), Busenberg and Plummer (1985), Kitano (1990), Bar-Matthews et al (1993), Tsukamoto and Tsukamoto (1995), Mitsuguchi et al (2001), Ramos et al (2004) Sr/Ca 8.0−10.0 Weber (1973), Polyakov and Krasnov (1976), Goreau (1977), Smith et al (1979), Oomori et al (1982), Schneider and Smith (1982), Beck et al (1992), de Villiers et al (1994, Fallon et al (1999Fallon et al ( , 2003, Gagan et al S/Ca 4.0−10.0 Tokuyama et al (1972), Oomori et al (1982), Busenberg and Plummer (1985), Kitano (1990), Bar-Matthews et al (1993), Tsukamoto and Tsukamoto (1995) F/Ca 3.0−7.0 Carpenter (1969), Ohde et al (1978), Ohde and Ramos (2004), Ramos et al (2005) Mg/Ca 2.5−6.5 Chave (1954), Weber (1974), Goreau (1977), Oomori et al (1982), Mitsuguchi et al (1996Mitsuguchi et al ( , 2001Mitsuguchi et al ( , 2003Mitsuguchi et al ( , 2008, Sinclair et al (1998), Fallon et ...…”
Section: Methodsmentioning
confidence: 99%
“…The sequence of preference with respect to dissolution in seawater was Mg > Ca > Sr [Schroeder, 1969]. Amiel et al [1973] also found incongruent dissolution for Mg/Ca but reported congruent dissolution for Sr/Ca. Recently, incongruent dissolution of Mg, Sr, and Na relative to Ca from powered coral aragonite has been observed in laboratorybased, freshwater-leaching experiments [Fairchild and Killawee, 1995;I.…”
Section: Introductionmentioning
confidence: 99%
“…TRACE METAL CONCENTRATIONS in coral skeletal aragonite have been suggested to reflect concentmtions in surface seawater (AMIEL et al, 1973;SCHNEIDER and SMITH, 1982;HOWARD and BROWN, 1984;SHEN, 1986;SHEN and BOYLE, 1988). Banded aragonitic corals have been useful recorders of surface water composition changes over time because annual and sub-annual sections can be assigned ages based on growth patterns.…”
mentioning
confidence: 99%